Analisis kinerja keuangan perusahaan rokok yang terdaftar di Bursa Efek Indonesia - Dien, Nita Teresia; Alexander, Stanly W.; Latjandu, Lady Diana (Yayasan Widyantara Nawasena Raharja, 2025)
Financial performance indicates how a company is doing over a given period. It encompasses how money is raised and distributed. This is measured using indicators such as capital adequacy, liquidity and profitability. This study will analyse the financial performance of companies in the cigarette sub-sector listed on the Indonesia Stock Exchange between 2020 and 2022. The Du Pont System Analysis will be used for this purpose. The research is qualitative, taking a descriptive approach with quantitative data. The study clearly shows that PT Gudang Garam Tbk's financial performance is still below par, as measured by its NPM value of 4.46% and ROI of 6.39%. These figures are below the industry average, indicating the need for improvements. However, the TATO value of 1.42 is effective because it is above the industry average. PT HM Sampoerna Tbk has an NPM of 7.40%, an ROI of 11.70%, and a TATO of 1.92. This demonstrates that the company is performing effectively. This is assessed against the average industry standard, which is above average for cigarette companies. PT Indonesian Tabacco Tbk is undoubtedly less effective. This is evident from the fact that the company's NPM, ROI and TATO values are all below the industry average. PT Wismilak Inti Makmur Tbk's NPM of 7.29%, ROI of 10.51%, and TATO of 1.46 times the industry average prove that the company is effective. These values clearly exceed the industry average.